Macrozoobenthos as Bioindicator of River Water Quality in Ciliwung Hulu Sub Watershed - Hamdani Rachman; Agus Priyono; Yusli Wardiatno (Media Konservasi, 2016)
Macrozoobenthos has a relatively sedentary nature and the very limited movement which will directly affected in the event of changes in water quality, therefore markozoobenthos often used as bio-indicators of water quality. This research was conducted form March to June 2015 in the Ciseuseupan sub watershed, Cisukabirus sub watershed and Cisuren sub watershed with the purpose of determining level of water quality and influence of land-use on the quality water by using macrozoobenthos community structure. Biological indices were used to analyze the macrozoobenthos are FBI and SIGNAL2. FBI values in the Ciseseupan sub watershed are 5,02 with criteria the quality of water moderate, in Cisukabirus sub watershed are 3,96 with criteria the quality of water very good and in Cisuren sub watershed 4,37 with criteria the quality of water good. Extensive use of forest land larger than the residential land use in Cisukabirus sub watershed were the major factor in the high quality in the sub watershed Kata kunci: land use, macrozoobenthos, water quality